Penerapan Pendekatan Keterampilan Proses Untuk Meningkatkan Hasil Belajar Sains Pada Siswa Kelas V SDN No. 2 Sikara Kecamatan Sindue Tobata - Mustimah, Mustimah (Jurnal Kreatif Tadulako Online, 2016)
The main problems in Classroom Action Research (CAR) is the low activity of the learning outcomes of students of class V No. SDN. 2 Sikara through process skills approach to the material work in a simple tehknology learning Science. This study aims to improve the learning outcomes of students in learning science through process skills approach. This research was conducted in the Village District of Sindue Tobata Sikara Donggala, on November 4, 2013 until November 11, 2013. Instrument consists of data collection: observation of teacher activity sheets, observation sheets assessment of student learning activities, and test evaluation of learning outcomes. The action research took place in two cycles. The results of the first cycle and second observations showed that students and teachers in learning activities and effective assessment of students who continue to rise to the very good category. Based on the analysis of the results of tests on the first cycle of students who completed 5 of 8 students, 62.5% completed the classical, the second cycle students who complete 8 of 8 students, classical 100% complete. Based on these results it can be concluded that the use of process skills approach can improve student learning outcomes science class No. 2 SDN Sikara. Keywords: Process Skills Approach, Results Learning Science